(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
In this article, the strength of reinforced concrete beams reinforced with basalt fibers in the slope section was studied experimentally and theoretically. The role of fibers in the concrete structure, their effect on crack elimination and their contribution to shear strength were analyzed. According to the results of laboratory tests, it was found that basalt fibers increase the shear strength and energy absorption capacity of concrete in the slope section. The results of the studies were compared with ordinary reinforced concrete, and suggestions were made on the optimal fiber content.